2005
DOI: 10.2337/diabetes.54.4.1164
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation of Insulin (Exubera) Is Associated With Augmented Disposal of Portally Infused Glucose in Dogs

Abstract: The results of the present study, using the conscious beagle dog, demonstrate that inhaled insulin (INH; Exubera) provides better glycemic control during an intraportal glucose load than identical insulin levels induced by insulin (Humulin) infusion into the inferior vena cava (IVC). In the INH group (n ‫؍‬ 13), portal glucose infusion caused arterial plasma glucose to rise transiently (152 ؎ 9 mg/dl), before it returned to baseline (65 min) for the next 2 h. Net hepatic glucose uptake was minimal, whereas non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
1

Year Published

2005
2005
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 30 publications
2
28
1
Order By: Relevance
“…Although the reasons for this are not clear, it is possible that 1) the FPG decrease with inhaled insulin relates to IAbs functioning as a repository that slowly releases insulin (22) (however, no correlation between insulin binding and FPG has been observed to date with this preparation) or 2) the inhalation of insulin may increase insulin sensitivity or reduce endogenous glucose release (23,24).…”
Section: Safety and Tolerabilitymentioning
confidence: 95%
“…Although the reasons for this are not clear, it is possible that 1) the FPG decrease with inhaled insulin relates to IAbs functioning as a repository that slowly releases insulin (22) (however, no correlation between insulin binding and FPG has been observed to date with this preparation) or 2) the inhalation of insulin may increase insulin sensitivity or reduce endogenous glucose release (23,24).…”
Section: Safety and Tolerabilitymentioning
confidence: 95%
“…These observations raise the question whether there is a unique glucose-lowering effect associated with insulin delivered by inhalation, although that study was not specifically designed to test the bioefficacy of insulin delivered by inhalation compared with s.c. injection. Recently, we demonstrated that enhanced nonhepatic glucose clearance is indeed associated with the pulmonary route of insulin administration compared with intravenous insulin infusion (Edgerton et al, 2005). Therefore, the second aim of the present study was to further investigate the apparent unique effect of insulin inhalation on increased insulin sensitivity.…”
mentioning
confidence: 99%
“…The possibility that 'the inhalation of insulin may increase insulin sensitivity or reduce endogenous glucose release' comes from trials in dogs [5,6]. In a first trial, inhaled insulin as compared with insulin infused in the portal vein increased non-hepatic glucose clearance for up to 3 h [5].…”
Section: Abbreviations Fpg: Fasting Plasma Glucosementioning
confidence: 99%
“…The possibility that 'the inhalation of insulin may increase insulin sensitivity or reduce endogenous glucose release' comes from trials in dogs [5,6]. In a first trial, inhaled insulin as compared with insulin infused in the portal vein increased non-hepatic glucose clearance for up to 3 h [5]. In a second trial, the amount of glucose needed to maintain euglycaemia over 6 h was 20% higher in the inhaled group than in the group that received subcutaneous insulin, despite similar insulin AUCs [6].…”
Section: Abbreviations Fpg: Fasting Plasma Glucosementioning
confidence: 99%